A comparative investigation of the effects of blue, red and far-red light qualities on the population growth and senescence of lemna minor L. and spirodela polyrhiza (l.) schleid species of lemnaceae - Villafaña, Abel P. 1944- (1976)
This investigation is an attempt to compare the effects of the blue, red, and far-red light qualities in the population growth of Lemma minor L. and Spirodela polyrhiza (L.) Schleid species of Lemnaceae. Light was modified by using colored cellophanes. The two species of duckweeds were collected, identified and cultured for this study. Pond water taken from the College of Arts and Sciences, UP Diliman, Quezon City served as the medium for the growth of each of the two species. The study shows the feasibility of using L. minor and S. polyrhiza to demonstrate the effect of varying light qualities on the growth of plant populations with effective results.